Chargino and neutralino production in the 3-3-1 supersymmetric model in e-e- scattering - Capdequi-Peyranère, M.; Rodriguez, M. C. [UNESP] (American Physical Society (APS), 2002)
The goal of this article is to derive the Feynman rules involving single charginos, neutralinos, double charged gauge bosons, and sleptons in a 3-3-1 supersymmetric model. Using these Feynman rules we calculate the production of double charged charginos with neutralinos and also the production of a pair of single charged charginos, both in an electron-electron linear collider. © 2001 The American Physical Society.